The Effect of the Covid-19 Pandemic on Mental Health (Children, Adolescents, Young Adults) and Mental Health Service: Systematic Review (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
The impact of the COVID-19 pandemic on mental health in young age groups (children, adolescents, and young adults) has a higher prevalence than individuals at other stages of the lifecycle (adults and the elderly). The implementation of mental health services faces more barriers to professional care than in the pre-pandemic period. This study aims to identify the effect of sociodemographic and Public Health Measures on the mental health of young age groups and mental health services during the COVID-19 pandemic. A systematic review without meta-analysis was performed on seven databases. The selection procedure followed the flow diagram of the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA). Inclusion criteria included all types of research that looked at the impact of COVID-19 on mental health and mental health services. There are 44 included articles and the quality assessment shows that the study was evaluated as 80% and 100% quality criteria met. During the implementation of Public Health and Social Measures, the young age group experienced mental health problems, including stress, depression, anxiety, sleeping disorder, eating disorder, and post-traumatic stress disorder related to socioeconomic status, academic, and social factors. This systematic review proves that the COVID-19 pandemic affects the mental health of the young age group and mental health services.